Determination of gene products and coding regions from the murE-murF region of Escherichia coli. - Maruyama, I N (1988)
We report the cloning of murE and murF genes and the identification of their gene products. The murE and murF genes encode diaminopimelic acid- and D-alanyl-D-alanine-adding enzymes, respectively, and both genes are involved in cell wall peptidoglycan biosynthesis in Escherichia coli.